EFFECT OF OBESITY ON QUALITY OF LIFE IN MIDDLE AGED FEMALES (International Journal of Physiotherapy, 2016)
Background: Obesity is increasing at an alarming rate across the world. Obesity has great impact on quality of life of individuals. Due to the fact that there is global increase in obesity, knowledge about the effect of obesity on quality of life in middle aged females is of great importance for physicians and physiotherapists with regard to improve the quality of life. Therefore, the purpose of study was to investigate the impact of obesity on quality of life in middle-aged females.Methods: Forty females participated in the study with a mean age of 48.05 years. According to their body mass index (BMI), Group 1 consists of normal weight females (n=20, BMI=18.5 -24.9) and Group 2 consists of obese females (n=20, BMI = >30). The Impact of Weight on Quality of Life (IWQOL) Questionnaire was used to assess the impact of obesity on quality of life.Results: There were significant differences (P